Energy and environmental assessments of bioethanol production from Sri Kanji 1 cassava in Malaysia - Hanif M.; Mahlia T.M.I.; Aditiya H.B.; Bakar M.S.A. (Green Wave Publishing of Canada, 2023)
Bioethanol; Emission control; Energy balance; Energy efficiency; Energy utilization; Ethanol; Gas emissions; Greenhouse gases; Plants (botany); Sustainable development; Bio-ethanol production; Biofuels policies; Energy assessment; Energy sustainability; Environmental assessment; Greenhouse gas balance; Malaysia; Renewable fuels; Sri kanji 1 cassavum; Transportation sector; Life cycle